Expression of Tlx in both stem cells and transit amplifying progenitors regulates stem cell activation and differentiation in the neonatal lateral subependymal zone - Obernier, Kirsten; Simeonova, Ina; Fila, Tatiana; Mandl, Claudia; Hölzl-Wenig, Gabriele; Monaghan-Nichols, Paula; Ciccolini, Francesca (Stem cells, 2011)
Niche homeostasis in the postnatal subependymal zone of the lateral ventricle (lSEZ) requires coordinated proliferation and differentiation of neural progenitor cells. The mechanisms regulating this balance are scarcely known. Recent observations indicate that the orphan nuclear receptor Tlx is an intrinsic factor essential in maintaining this balance. However, the effect of Tlx on gene expression depends on age and cell-type cues. Therefore, it is essential to establish its expression pattern at different developmental ages. Here, we show for the first time that in the neonatal lSEZ activated neural stem cells (NSCs) and especially transit-amplifying progenitors (TAPs) express Tlx and that its expression may be regulated at the posttranscriptional level. We also provide evidence that in both cell types Tlx affects gene expression in a positive and negative manner. In activated NSCs, but not in TAPs, absence of Tlx leads to overexpression of negative cell cycle regulators and impairment of proliferation. Moreover, in both cell types, the homeobox transcription factor Dlx2 is downregulated in the absence of Tlx. This is paralleled by increased expression of Olig2 in activated NSCs and glial fibrillary acidic protein in TAPs, indicating that in both populations Tlx decreases gliogenesis. Consistent with this, we found a higher proportion of cells expressing glial makers in the neonatal lSEZ of mutant mice than in the wild type counterpart. Thus, Tlx playing a dual role affects the expression of distinct genes in these two lSEZ cell types.
Gesehen am 29.09.2022